Bacteriological Quality of Tableware in Culinary Tourism Centers - Frisakti Iftita, Maura Vionabella; Rusmiati, Rusmiati; Sari, Ernita; Suprijandani, Suprijandani (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Culinary centers should pay attention to washing tableware if it is not good enough to cause health problems.  Microbiological preliminary tests in the culinary tourism center calculated the number of germs on 12 tableware traders and found that six tableware did not meet the requirements.  This study aims to determine the process of washing tableware in culinary centers; this study was a descriptive study with purposive sampling.  Data collection used observations and laboratory tests, which were analyzed descriptively using tables in the form of narrative; the examination of tableware in the form of plates, spoons, forks, and glasses found germ numbers.  At the same time, the examination of the clean watered coliform total parameter was 48 CFU/m2.  The washing process obtained results of 60% qualified and 40% did not qualify because it did not comply with the provisions; the conclusion of this study was found the number of germs on tableware, as well as clean water on the total coliform parameters were not qualified, in the washing process most of them were not competent, so the advice of the researcher was that traders must pay attention and increase knowledge about the technique of washing tableware and draining the watered reservoir regularlyments below. I thanked everyone for their suggestions on how to improve this converter.